(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background – Critical appraisal of AETCOM Module with reference to Bioethical inclusions vis-à-visprofessional ethics inclusions needs appraisal for purposes of judicious operational mix of two, so thatlearner is oriented in all-round manner so that optimal results thereto stand generated with at par status incommensuration with “The UNESCO Universal Declaration On Bioethics And Human Rights”.Methods – Rapid review of literature with reference to AETCOM Module for identification of Bioethicalinclusions in it with reference to Bioethical principles included in UNESCO declaration specially thoseapplicable to profession and not propagation or advocacy. Critical appraisal of identified Bioethicalinclusions with reference to their conformity with bioethical principles as applicable to profession includedin UNESCO declaration and to work out appropriate inclusion of non-included bioethical principles in formof structured competencies and their incorporation in AETCOM module with reference to their placement,learning levels , mode of assessment.Conclusion –This study deals with mapping and matching of competencies included in AETCOM modulewith UNESCO universal declaration on human rights and bioethics giving recommendations which canfulfil realised omissions in present AETCOM module thereby leading to its simplification and adoption.